Implementation of Village Fund Allocations in The Food Security Program in Karya Village, Pakkat Subdistrict, Humbang Hasundutan Regency, in 2025 - Iqnatia Patricia Manalu; Nazaki Nazaki; Ardi Putra (Anthroposia: Journal of Social and Human Development, 2026)
Food security is one of the national priority programs supported through the use of Village Funds in Karya Village, Pakkat District, Humbang Hasundutan Regency. The food security program is implemented through capital participation in the Village-Owned Enterprise (BUMDes) for a chicken farming business and the provision of corn seed assistance to the community. However, several problems remain in its implementation, such as limited community understanding of the program mechanism, suboptimal coordination among implementers, and limited monitoring and evaluation. This study aims to analyze the implementation of the use of Village Funds in the food security program in Karya Village in 2025. This study uses a qualitative method with a descriptive approach, with data collected through observation, interviews, and documentation. This study applies George C. Edward III's policy implementation theory, which covers communication, resources, disposition, and bureaucratic structure. The results show that the implementation of Village Fund use in the food security program in Karya Village has generally been carried out in accordance with applicable provisions. In terms of communication, program socialization has been carried out through village deliberation, although community understanding remains uneven. In terms of resources, budget support, human resources, and infrastructure are considered adequate to support program implementation. In terms of disposition, program implementers demonstrated good commitment to carrying out food security activities. Meanwhile, in terms of bureaucratic structure, program implementation has involved various parties, but coordination and oversight still need to be strengthened. Based on the findings, it can be concluded that the implementation of Village Fund use in the food security program in Karya Village has run reasonably well, although its effectiveness still needs to be improved through stronger coordination, oversight, and community understanding so that the village's food security goals can be optimally achieved